SURVEY OF FISH DISEASES IN RANYA (RAPARIN ADMINISTRATION)/ SULAIMANIYA GOVERNORATE; CASE STUDY - Nasreen Mohi Alddin Abdulrahman; Adel Jabbar Hussein; Sulaiman Salah Sulaiman; Brwa Abbdulla Rasul (Basrah Journal of Veterinary Research)
This study tends to survey of common problems and diseases of fish aquaculture projects atRaparin administration area which have 76 projects, three species of Cyprinidae, common carp, grasscarp, silver carp, in earthen and concrete ponds. By achieve the history of the disease outbreaks andunderstanding management strategies which applied by farmers, on this bases the collection of samplesfrom different cases at different regions of Raparin area, clinical examinations done. The results of thisstudy indicate the blow diseases and problems of fish aquaculture projects. Bacterial infections,hemorrhagic septicemia, Bacterial enteritis, Infectious dropsy, skin ulceration. Fungal infections,Saprolegniosis, epizootic ulcerative syndrome. Parasitic infections, Gyrodyctylus infection,Ductylogyrus infection, Argulosis. Bad management represented by poor nutrition, low applyingoxygen, and bad water quality.